High-Mobility Group Box 1 (Hmgb1) Protein Evaluation in Mptp-Induced Zebrafish Model of Parkinson’s Disease - Mohamed, Wael; Razali, Khairiah; Othman, Noratikah; Hamza, Mohamed; Doolane, Abdel, Moneem; Kumar, Jaya; Ibrahim, Wisam, Nabeel (My University, 2021)
Molecular studies have proven beneficial in understanding the pathophysiology of PD. Besides, the advancing application of zebrafish as a PD model has enabled researchers to conduct molecular studies with more promising outcomes and significance. Current evidence reported on the association of HMGB1 protein with neuroinflammation-induced PD pathogenesis. However, to the extent of our knowledge, the molecular mechanism pertaining to HMGB1 involvement in PD are still elusive. Hence, we propose to conduct a study on HMGB1 protein, to elucidate its role in the pathogenesis of the MPTP-induced zebrafish model of PD. This study will answer the question pertaining to the involvement of HMGB1 in PD development and whether the knockdown of this protein can improve PD symptoms in zebrafish, particularly MPTP-induced motility disorders.
Keywords: HMGB1; PD; ZF